The Impact of Social Support and Health Literacy on CERDIK Practices Among Type 2 Diabetics in Rural Indonesia - Narmawan, Narmawan; Seri Yuliana, Hartalia; Aldin , Reimon; Narmi, Narmi (PT. Nursing Genius Care, 2025)
Background: The CERDIK program (Check, Eat, Regular exercise, Drugs, Insulin injection, and Control blood glucose) is a key self‑management strategy for Type 2 Diabetes Mellitus (T2DM). However, patient adherence remains suboptimal in many primary health care settings.Objective: To identify family support, diabetes knowledge, and motivation as factors associated with CERDIK behavior among T2DM patients at Puskesmas Moramo.Methods: A cross‑sectional study was conducted in May 2024 among 42 T2DM patients attending Puskesmas Moramo. Participants were recruited by consecutive sampling. Data were collected using validated questionnaires for family support, diabetes knowledge, motivation, and CERDIK behavior (Cronbach’s α = 0.82–0.90). Spearman’s rank correlation was performed in SPSS v26 with α = 0.05.Results: The mean age was 57.3 ± 8.5 years; 58.3% were female. Good CERDIK behavior was observed in 24 (57.1%) patients. Family support was moderately correlated with CERDIK behavior (ρ = 0.483; p = 0.001). Diabetes knowledge (ρ = 0.395; p = 0.008) and motivation (ρ = 0.317; p = 0.035) also showed significant positive correlations with CERDIK behavior. Conclusion: Family support, diabetes knowledge, and motivation are significant factors influencing CERDIK behavior in T2DM patients at Puskesmas Moramo. Interventions should integrate family involvement, targeted education, and motivational enhancement to improve self‑management and glycemic outcomes.